Mobile training and support (MOTS) service—using technology to increase Ebola preparedness of remotely-located community health workers (CHWs) in Sierra Leone - Kenna, Paula Mc; Babughirana, Geoffrey; Amponsah, Monica; Egoeh, Seth Gogo; Banura, Evelyne; Kanwagi, Robert; Gray, Bobbi (mHealth, 2019)
Background: The Ministry of Health in Sierra Leone has developed and operationalized the national Digital Health Strategy to guide integrated roll out of e-health/mobile health solutions. The goal is that “by 2023 an effective and efficient ICT enabled system supports delivery of quality, accessible, affordable, equitable, and timely healthcare services and moves Sierra Leone closer to achieving universal health coverage”. Investing in digital platforms for the education of community health workers (CHWs) in Sierra Leone is a critical strategic approach to strengthening the country’s readiness for future Ebola outbreaks. A new national curriculum for this target group is being implemented that is based upon classroom training approaches. In a country where many CHWs are remotely located, the use of technology can be an enabler to reach such individuals with key training content to repeat the most important messages. Here we describe the piloting of a mobile training and support (MOTS) service for CHWs using interactive voice response (IVR) technology in Bo district of Sierra Leone. This training platform delivers voice recorded training content in local languages on the topics of Vaccines and (Ebola) Disease Surveillance & Outbreak Response. Methods: MOTS was developed in collaboration with the Sierra Leone Ministry of Health & Sanitation. Training content was customized in line with the national training curriculum and case reporting requirements. Local ethical approval was achieved and a test protocol involving recruitment of 125 consenting CHWs was implemented in Bo district of Sierra Leone. Two training modules—one covering vaccination and one covering outbreak response and disease surveillance were delivered to the mobile phones of participants as audio messages in the preferred local language. Knowledge change was assessed largely through pre- and post-quiz assessments also implemented through IVR. Results: Knowledge acquisition was observed in the 123 CHWs completing this pilot assessment. The extent of knowledge acquired was higher with the Vaccine training module when compared to the (Ebola) Disease Surveillance & Outbreak Response module. The technology was readily accepted by this population and their engagement was such that they also provided important elements to be improved prior to further implementation. The order in which training modules are delivered as well as general fatigue of the IVR methodology for participating in the quiz assessments may be of importance and requires further investigation. Conclusions: Technology should be considered when planning delivery of training to CHWs and can be positioned as a vehicle by which repetitive aspects of important training content can be reinforced without the need for additional classroom presence of the CHW community. Sustainability of such solutions requires cost containment and subsequent software accessibility for authorities in resource limited settings. Transparent partnership and alignment with the Ministry of Health & Sanitation in Sierra Leone from the outset of this project is considered an important element to ensure successful implementation.